Visualising China, 1845-1965 : moving and still images in historical narratives - Henriot, Christian; Yeh, Wen-Hsin (China studies (Leiden, Netherlands), 2012)
In Visualizing China, the authors launch a broad inquiry aimed at a synergistic understanding of the story of visuality in modern China. The essays cluster around several nodal points including photographs, advertising, posters and movies, from the 1840s to the 1960s.